2020
DOI: 10.1108/ec-01-2020-0046
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure and heat transfer analysis of the floatation nozzle with a moving wall

Abstract: Purpose This study aims to investigate the effects of different surface-to-jet velocity ratios (Rsj) on the flow structure and the heat transfer of the floatation nozzle under different ratios (h/w) of the separation distance (h) to the slot width (w) and the differences of the flow structure and the heat transfer between the floatation nozzle and the slot nozzle. Design/methodology/approach The Nusselt number (Nu) and the pressure distribution of the floatation nozzle with a stationary wall are measured. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This implies the resistance of the circulating flows to the shear effect induced by the motion of the plate is relatively high at h / e = 8. 44 Furthermore, with increasing h / e , individual flow structures are easily recognizable, implying that the integrity of the flow structures is high. At high R V , such a tendency is even more prominent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies the resistance of the circulating flows to the shear effect induced by the motion of the plate is relatively high at h / e = 8. 44 Furthermore, with increasing h / e , individual flow structures are easily recognizable, implying that the integrity of the flow structures is high. At high R V , such a tendency is even more prominent.…”
Section: Resultsmentioning
confidence: 99%
“…For the former, the peaks of Nu are related to the impingement of the circulating flow on the plate, leading to net convective heat flux and enhanced heat transfer. 44,48,49 The peaks of Nu between the two nozzle units are related to the wall jets and the interaction between the two jet streams and the plate. Consequently, local heat transfer is enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of a few minor characteristics, such as the placement of the air intake, the experimental boundary conditions employed in this investigation are essentially the same as those found in the literature 22 . We can more readily determine which turbulence model is more accurate by comparing its output with the experimental data, as this allows us to cross-check the model's correctness.…”
Section: Model Validation Analysismentioning
confidence: 99%
“…The wall motion also has a great influence on the heat transfer and pressure characteristics. The research results of Huang et al 22 show that the distribution of Nu (Nusselt number) in suspension nozzle area 2 increases with the increase of Rsj , and when Rsj < 0.05, the local distribution of Nu on the wall basically does not change, while the distribution of Cp (Pressure coefficient) is basically not affected by Rsj . However, Sharif et al 17 studied the influence of wall movement on heat transfer and found that when Rsj < 0.1, the local Nu distribution of the wall basically did not change.…”
mentioning
confidence: 99%
“…Due to its higher efficiency in heat transfer and drying without contact with the substrate, the floatation nozzle has gained considerable attention. It has been applied in various industrial fields such as paper drying [1], printed electronics [2], textile drying [3], and the drying of lithium-ion battery electrodes [4], etc. Figure 1 shows a floatation nozzle drying system.…”
Section: Introductionmentioning
confidence: 99%